Effect and Process Evaluation of an Intervention to Promote Physical Activity Among White-collar Employees at a Public University: The Profit-study - Cheah, Yong Xiang; Cheah, Whye Lian; Helmy, Hazmi (UPM, 2025)
Introduction: The ProFit (Promote Fitness) study was a multi-component workplace environmental intervention to enhance participants' physical activity (PA). This study utilized a dual approach to determine the intervention's effects on MET-min/week and steps/week over time, and to evaluate whether the intervention effects differed based on process evaluation scores (PES) in the ProFit study. Materials and methods: This six-month, two-group, parallel, quasi-experimental study included 11 eligible workplaces, which were randomly assigned to either intervention group (IG) or control group (CG) in a 1:1 ratio. Each group had 84 participants. The IG received intervention, while CG maintained their usual routines. PA levels were measured at baseline, mid-intervention, and post-intervention using the International Physical Activity Questionnaire and pedometers. Repeated measures ANOVA was employed to analyze changes over time. PES for IG participants were calculated post-intervention to evaluate implementation dynamics. Results: Although no significant differences were found between IG and CG over time, the IG demonstrated significant improvements in total MET-min/week (ηp2=0.031), housework-related PA (ηp2=0.101), and steps/week (ηp2=0.827). The mean PES of 28.65 out of 35 indicated effective intervention implementation. Participants in the high-PES category experienced significant increases in total steps/week (p<0.001) and total MET-min/week (p=0.039) compared to those in the low-PES category. Conclusion: This intervention effectively improved PA levels in IG. Those in the high-PES category achieved significantly better post-intervention outcomes. These findings highlight the ProFit study's potential to promote PA and provide valuable insights for employers and researchers